Transmission line parameter error detection, identification and correction with geometrical view: Topological errors - Bretas, Newton G.; Martins, Andre C.P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
In this paper it is proposed an approach to detect, identify and correct series and shunt branch parameter errors of a transmission line using a geometrical view. Firstly it is tested if any of the measurement equations have a gross error using the J(x) index, but with the measurement error as the objective function. Next, to conclude for transmission line i-j parameter error, the corresponding measurements associated to that line should have the Composed Normalized Error CNEi-j superior to the chosen threshold value. Also, the error will spread to the measurements of the neighborhood. The correction in the parameter is made using the corresponding measurement CNE. The proposed approach uses only one measurement snapshot. Using the geometrical view, two kinds of topological errors are analyzed: (i) very large parameter errors; (ii) short circuit of a line. To test the procedure efficiency the IEEE 39-bus network will be used.
Keywords: Bad Data Detection; Geometric Interpretation; Innovation Index; Parameter Error Detection and Identification; Parameter Estimation; State Estimation